Páginas da memória: A escrita do trauma em Diário da queda, de Michel Laub - Barbara Luiza Vilaca dos Santos (2018)
This dissertation consists in the study of the novel Diary of the Fall (2011), written by the Brazilian author Michel Laub. Based on two pillars, the storyline and the form, this paper approaches to the literary text, broaching its intrinsic elements. Trauma and memory are connected with repetition, fragmentation and flow of ideas. The mirroring between the characters, also visible in the narrative formal construction, which returns to recurrent scenes and words, is analyzed, as well as the possible maintenance of a cycle that is presented in the thematic and in the structure in a narrative that goes backwards and forwards. Through those elements, our work aims the development of a reinterpretation of the book, in means of discuss the end of the novel as inconclusive and ironic. Moreover, is observed the insertion of Diary of the fall in the collection of Michel Laubs work, recognizing the presented aspects as inherent in his poetics.